Text mining techniques for healthcare provider quality determination : methods for rank comparisons - Cerrito, Patricia B. (Medical Information Science Reference, 2010)
"This book discusses defining a patient severity index for risk adjustments and comparison of patient outcomes to assess quality factors"--Provided by publisher.